High-fat diets cause insulin resistance despite an increase in muscle mitochondria - Hancock, Chad R. (National Academy of Sciences, 2008)
It has been hypothesized that insulin resistance is mediated by a deficiency of mitochondria in skeletal muscle. In keeping with this hypothesis, high-fat diets that cause insulin resistance have been reported to result in a decrease in muscle mitochondria. In contrast, we found that feeding rats high-fat diets that cause muscle insulin resistance results in a concomitant gradual increase in muscle mitochondria. This adaptation appears to be mediated by activation of peroxisome proliferator-activated receptor (PPAR)δ by fatty acids, which results in a gradual, posttranscriptionally regulated increase in PPAR γ coactivator 1α (PGC-1α) protein expression. Similarly, overexpression of PPARδ results in a large increase in PGC-1α protein in the absence of any increase in PGC-1α mRNA. We interpret our findings as evidence that raising free fatty acids results in an increase in mitochondria by activating PPARδ, which mediates a posttranscriptional increase in PGC-1α. Our findings argue against the concept that insulin resistance is mediated by a deficiency of muscle mitochondria.